MPH Field Experience at Jackson County Missouri Health Department - Bhatt, Pranav (My University, 2013)
The Jackson County Health Department is located in Independence, Missouri. It is affiliated with Truman Medical Centers, Kansas City, MO. For more than 80 years the Jackson County Health Department has been dedicated to preventing disease, promoting healthy lifestyles and protecting our communities and environment. The health department was established as a unit in January 1925 and provided communicable disease control, examination and immunization of school children, and teaching classes in home hygiene and care of the sick. Today, serving over 250,000 residents, Jackson County Health Department continues its dedication to the prevention of disease and the maintenance of quality health for families and the community through education, immunization, inspection and supportive care.
Keywords: Public Health; Jackson County Missouri; Disease Prevention; Public Health (0573)